WEBSITE DEVELOPMENT USING A STEM APPROACH TO SIMPLE AIRCRAFT MATERIAL TO IMPROVE STUDENTS' CREATIVE THINKING SKILLS - Rahayu, Destiana; Khoiri, Ahmad; Lailiyah, Siti (Universitas PGRI Sumatera Barat, 2025)
This study aims to develop website-based learning media with a STEM approach on simple aircraft material to improve junior high school students' creative thinking skills. The method used is Research and Development (R&D) with the ADDIE model. Data were collected through observation, interviews, questionnaires, and tests in the form of pretests and posttests. Instruments include validation sheets, practicality questionnaires, and creative thinking tests. The validation results showed a score of 89% by material experts and 96% by media experts with a very valid category. Practicality by teachers was 80% with a practical category and students were 89% with a very practical category. The t-test showed a result of -22.681 (t <α, α = 0.05), and an n-gain of 0.6437 (moderate category). These results indicate that website-based media with a STEM approach is valid, practical, and effective in improving students' creative thinking skills.